Energy efficiency and sustainability assessment of about 500 small and medium-sized enterprises in Central Europe region. (June 2017) - Viesi, Diego; Pozzar, Francesca; Federici, Alessandro; Crema, Luigi; Mahbub, Md Shahriar
Abstract: Nowadays more than 20 million small and medium-sized enterprises (SMEs) are located in the European Union (EU): they are a key driver for economic growth, innovation, employment and social integration. The first step towards better industrial energy and environmental performance is the acknowledgement of the savings potential that can be realized by the company ownership and management board. Following this goal, the CEEM (Central Environmental and Energy Management) project provided to about 500 Central Europe SMEs of 5 countries (Austria, the Czech Republic, Hungary, Italy and Slovenia) a user friendly and free of charge web tool called 3EMT (Eco Energy Efficiency Management Tool). Through a questionnaire the 3EMT analyzes and sums up eco-energy patterns, helps to self-assess the company environmental performance, benchmarks a company with other Central Europe's enterprises, delivers a customized Assessment Report, suggests further services and facilities. In this paper, the large 3EMT database is analyzed, and statistics focused on SMEs eco-energy performance and future & innovation perspectives are presented and discussed. Furthermore, key challenges and key intervention points were defined by local stakeholders (policy makers, Energy Service Companies, SMEs representatives, researchers), this paper summarizes the main policy outcomes. Highlights: Evaluation of Central Europe SME performance in energy efficiency and sustainability. Extension of SME statistics at European and national level. Identification of key challenges and key interventions for new industrial policies.